The Role Of Parents And Families In Children's Education In The Digital Era - Burhan Nudin; Lukman; Wahyu Sihab; Nofri Aldinata; Muhammad Daffa Imaduddin; Triono (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem : Technology's rapid evolution presents both opportunities and challenges for children, affecting their education, communication, and exposure to risks like inappropriate content and cyberbullying. Balancing screen time with physical and social activities is a growing concern, prompting a need for updated parenting strategies in the digital age. Purpose : This study investigates the digital age's impact on children's upbringing, focusing on parental roles. It aims to understand technology's dual aspects—its benefits and risks—and offer guidance on adapting parenting methods to enhance children's safety, well-being, and development amidst technological changes. Design/methods/approach: A mixed methods approach is used, involving surveys and interviews with parents and educators. The research reviews literature on technology's effects on children and examines effective parental strategies for managing screen time and promoting digital literacy. A framework is developed to evaluate technology's influence and suggest parental engagement strategies. Findings : Excessive screen time links to developmental issues like attention problems, aggression, and health concerns. Technology also offers educational and social benefits. Strategies to mitigate negative impacts include setting limits, creating tech-free areas, and modeling responsible behavior. Engaging parents in digital education and discussing online safety are highlighted as essential. Research implications/limitations: The findings underscore the necessity for collaboration among parents, educators, and policymakers to manage the digital age's challenges. While technology is beneficial, it requires careful handling to safeguard children's welfare. Study limitations include potential biases in self-reported data and difficulties separating technology's effects from other factors. Originality/value : This research offers fresh insights into the technology-child development relationship, providing actionable advice for parents and educators. It bridges theory and practice, enriching discussions on safely and effectively navigating the digital age.